2020
DOI: 10.5586/aa.7311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palm Leaf Biochar on the Availability of Soil Nutrients, Leaf Nutrient Concentration, and Physiological Characteristics of Melon Plants (Cucumis melo L.) Under Drought Stress

Abstract: To investigate the effect of palm leaf biochar on the element absorption and reduction of drought stress effects in melon plants, an experiment was conducted using a split plot in a randomized complete block design with three replications in two successive years. The main plot contained three levels of drought stress (60%, 85%, and 100% water requirement) and the subplot contained four levels of biochar (0, 150, 300, and 450 g per plant). The results revealed that biochar application reduced the effect of drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…These results showed that even at the lowest considered f BC , among those considered, BC addition could be a useful strategy when DI is practiced for cultivation of wheat and tomato, under the extremely arid conditions of the considered study area and/or similar climatic areas. Our results agree with those obtained by Bagheri et al [77] in Iran, indicating that the use of biochar can be a successful strategy for improving water use efficiency and reducing the effects of drought stress under extremely arid climates and for soils characterized by very poor soil water retention, as the desert sand considered in this investigation.…”
Section: Resultssupporting
confidence: 92%
“…These results showed that even at the lowest considered f BC , among those considered, BC addition could be a useful strategy when DI is practiced for cultivation of wheat and tomato, under the extremely arid conditions of the considered study area and/or similar climatic areas. Our results agree with those obtained by Bagheri et al [77] in Iran, indicating that the use of biochar can be a successful strategy for improving water use efficiency and reducing the effects of drought stress under extremely arid climates and for soils characterized by very poor soil water retention, as the desert sand considered in this investigation.…”
Section: Resultssupporting
confidence: 92%
“…In crop production, attention is given to biostimulants, defined as organic or inorganic substances, microorganisms that are capable of mitigating the adverse effects of stress, or both, improving plant growth and productivity [32]. Bagheri et al [33] showed that adding palm leaf biochar to the soil, especially under drought stress conditions, reduces the rate of water use and improves the growth and yield of melon plants. Mycorrhizae improve plant tolerance to a range of abiotic stresses through various physiological, functional and biochemical changes in plants [34].…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit stress affects cellular turgescence, opening of stomata, photosynthesis processes, respiration and transpiration, and ultimately reduces crop yield (Bagheri et al, 2020;Darabad et al, 2020;Zhang et al, 2015). Fertilizers are used to supplement soil with essential nutrients to promote plant growth and increase crop productivity under normal and stress conditions (Cordell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%